2012
DOI: 10.1002/cbdv.201200139
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Hypericum rumeliacumBoiss. Essential Oil. A New Chemotype of This Pharmacologically Valuable Species?

Abstract: Analysis by GC and GC/MS of the essential-oil samples obtained from dry above-ground parts of Hypericum rumeliacum Boiss. (collected in the flowering and fruit-forming vegetative stages) allowed the identification of 212 components in total, comprising ≥97.8% of the total oil composition. In the flowering phase, the major identified volatile compounds were undecane (6.6%), dodecanal (10.8%), and germacrene D (14.1%), whereas α-pinene (7.3%), β-pinene (26.1%), (Z)-β-ocimene (8.5%), (E)-β-ocimene (10.2%), bicycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…In this study, monoterpenes (72.06%) were found to be the main class of compounds with α -pinene (9.89%), β -pinene (16.43%), β -myrcene (5.95%), and trans - β -ocimene (12.88%) being the most abundant compounds in this group ( Supplementary Table S6 ). When comparing the results of H. rumeliacum EO in this study with results obtained for the same species in previous reports [ 7 , 17 , 35 , 49 , 54 ], it appears that each of these studies found different dominant compounds. For example, 2-methyloctane (20.5%), α -pinene (13.7%), and spathulenol (9.8%) were the main EO compounds of samples from Serbia [ 17 ].…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…In this study, monoterpenes (72.06%) were found to be the main class of compounds with α -pinene (9.89%), β -pinene (16.43%), β -myrcene (5.95%), and trans - β -ocimene (12.88%) being the most abundant compounds in this group ( Supplementary Table S6 ). When comparing the results of H. rumeliacum EO in this study with results obtained for the same species in previous reports [ 7 , 17 , 35 , 49 , 54 ], it appears that each of these studies found different dominant compounds. For example, 2-methyloctane (20.5%), α -pinene (13.7%), and spathulenol (9.8%) were the main EO compounds of samples from Serbia [ 17 ].…”
Section: Resultssupporting
confidence: 65%
“…Secondary metabolites in plants have been successfully used as biomarkers in taxons [ 14 , 48 ]. There have been several published reports in which the authors looked for relationships between EO components as chemotaxonomic markers in the genus Hypericum [ 17 , 37 , 45 , 49 ]. However, because genetic and environmental conditions were the main factors that determined the composition of Hypericum EO, its components were deemed insufficient chemotaxonomical markers [ 17 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrocarbons, such as 3-mehtyl-nonane (12.3%), 2-methyl-octane (9.6%) and nonane (7.6%) were also present among main components of H. laricifolium essential oil in the current investigation; related components have also been reported, previously, in high concentrations for other Hypericum species [12,13,[15][16][17][18].…”
Section: Resultssupporting
confidence: 77%
“…H. elongatum also showed a large amount of α-pinene (80.43%) and determined β-pinene (2.59%) between the minor compounds [14]. However, H. rumeliacum showed higher concentrations of β-pinene (26.1%) comparing to α-pinene (7.3%) [15]. On the other hand, H. perforatum, known as the most commercially important species within the genus Hypericum, showed the presence of α-pinene (8.6%) and β-pinene (3.8%), along with germacrene-D (22.1%), β-caryophyllene (11.3%), α-cadinol (4.4%), 2-methyl-octane (3.7%), terpinen-4-ol (3.3%), caryophyllene oxide (3.3%), α-muurolol (2.9%) and spathulenol (2.8%) [16].…”
Section: Resultsmentioning
confidence: 99%